2012
DOI: 10.1007/s11999-012-2252-4
|View full text |Cite
|
Sign up to set email alerts
|

Operating Room Traffic is a Major Concern During Total Joint Arthroplasty

Abstract: Background Periprosthetic joint infection (PJI) is a challenging complication associated with total joint arthroplasty (TJA). Traffic in the operating room (OR) increases bacterial counts in the OR, and may lead to increased rates of infection. Question/purposes Our purposes were to (1) define the incidence of door opening during primary and revision TJA, providing a comparison between the two types of procedures, and (2) identify the causes of door opening in order to develop a strategy to reduce traffic in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
100
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 17 publications
7
100
0
1
Order By: Relevance
“…A previous study 11 reported a door opening rate of 0.65 door openings/min for primary TJA, which is similar to the rate of 0.64 door openings/min found in our study. The weakness of the previous study was a change during the investigation regarding counting start time, which could have modified their true rate of door openings per minute.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A previous study 11 reported a door opening rate of 0.65 door openings/min for primary TJA, which is similar to the rate of 0.64 door openings/min found in our study. The weakness of the previous study was a change during the investigation regarding counting start time, which could have modified their true rate of door openings per minute.…”
Section: Discussionsupporting
confidence: 92%
“…4 Door opening is believed to disrupt the laminar flow 5 and could thus lead to more bacteria and contamination over the wound and possibly lead to intraoperative infection. 4,[6][7][8][9][10][11] Thus far, only 1 study has measured the incidence of door opening during TJA. 11 Other studies defining OR traffic patterns were either not specific to orthopedic procedures or had a very limited number of orthopedic cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation may be that contamination of the sterile field occurs during the extended preoperative setup time. Possible contamination sources include direct contact with the sterile field, airborne contamination from traffic, 19 or loss of sterile technique. Dalstrom et al conducted a study in a simulated operating room environment and found a significant correlation between the length of time that the sterile tray is exposed to the air and the contamination rate of the instruments.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] In addition, ample evidence exists for deficits in hand hygiene during anesthetic care, [20][21][22][23][24] intraoperative patient warming during surgery, [19] and restricted traffic flow during surgical procedures. [25][26][27][28] These results show a substantial "knowdo gap" [29] between what is known about safe and effective practice and what is actually done in the OR, supporting an urgent need for implementing evidence-based practice for preventive innovations in order to enhance the safety of patients.…”
Section: Introductionmentioning
confidence: 86%